Human and Nature: Developing Virtues for Environmental Responsive Behaviour - Jena, Anita; Kar, Sarita (Problemy Ekorozwoju, 2023)
The environmental issues such as deforestation, climate change, ozone layer depletion, greenhouse effect and pollution of air, water and soil rises due to unethical activity of human beings and behaviour of humankind. Environmental degradation and the deterioration of human moral values are inter-connected with each other. So, environmental revolution required a transformation in human behaviour. Virtue ethics could be used as an instrument to develop a pro-environmental behaviour. Virtue ethics is primarily concerned with what kind of people we should be, what kind of characters we should have, and how we should act. This directly develops one’s moral character as well as pro-environmental character and behaviour, i.e., wisely use the natural resources; develop the habit to preserve the nature. Virtue ethics would be built to bridge the gap between human behaviour and the needs of environment. This paper emphasizes the implications of virtue ethics to bring changes in human character and behaviour to resolve the current environmental problems.